Defining the term of life of food products - Koval, Olha; Reznikov, Sergei (My University, 2013)
The authors proposed a theory modeling of food quality during storage. Computations are based on second order differential equations describing the kinetics of accumulation of harmful substances and the changes in the structural and mechanical properties.
Keywords: expiration date of food products; моделювання харчових продуктів; термін придатності харчових продуктів; кафедра технології ресторанної і аюрведичної продукції